Borrowing, the Outcome of Language Contact - Sabir, Paiman Hama Salih (Journal of University of Human Development, 2016)
This study which entitles “Borrowing, the Outcome of Language Contact” tackles one aspect of the current sociolinguistic phenomenon, which borrowing words by Kurdish speakers as the result of language contact. Due to the development of technology, globalization, and easiness of transportation among different countries, languages come into contact, as the result words are borrowed from one language to another and especially from the donor language to the recipient one. Since Kurdish language (as one of the world languages) is also been affected by the new trend of language contact, accordingly many words have been borrowed into all aspects of life. For this purpose, the researcher tries to define borrowing or loan words, classify them depending on literature and identifies the major factors on borrowing words, finally, the researcher presents a number of tables within which she represents a vast number of borrowed words from English, adapted from a study that she has done on English loan words used by Kurdish people at visual media.